The Founding Meeting of the Claims Conference and its Record - Creangă Ovidiu (Eastern European Holocaust Studies)
While the history of the Claims Conference has been documented, little is known about the meeting that established the organization over 70 years ago. This study examines the founding of the Claims Conference using its first record, the transcript of the meeting that took place at the Waldorf Astoria Hotel in New York City, on October 25–26, 1951. Many historical accounts about the Claims Conference offer cursory descriptions of its inception without examining the full scope of the debate underlying its founding. A few attempts in recent years have addressed this gap but a need for a more comprehensive analysis remains. This study explores the inaugural meeting through the lens of the organizations that took part in the conference and demonstrates the important role they played in shaping the outcome of the conference. By examining the transcript of that meeting in greater detail, this study contributes to a deeper understanding of the Claims Conference’s origin and of its subsequent history.